Resolved images of a protostellar outflow driven by an extended disk wind - Bjerkeli, Per; Wiel, Matthijs H. D. van der; Harsono, Daniel; Ramsey, Jon P.; Jorgensen, Jes K. (Nature, 2016)
Observations of the outflow associated with the TMC1A protostellar system reveal that the ‘disk wind’ model correctly explains how material is ejected from protostars.